POTENTIAL USE OF ZAKAT WAKALAH FOR SUSTAINABLE DEVELOPMENT OF ISLAMIC SOCIAL FINANCE - Siti Nor Amira Mohamad; Nurin Munirah Shahrul Nizar (Journal of Islamic, Social, Economics and Development, 2024)
Zakat Wakalah is essential for the sustainable development of Islamic social finance. However, previous studies need to pay more attention to its empowerment as there still needs to be a higher level of public trust in Zakat institutions and improper Zakat distribution in Malaysia. This has motivated the paper to explore the potential use of Zakat Wakalah for the sustainable development of Islamic social finance from practitioners. This study employed a qualitative approach in the form of semi-structured interviews. The interviews were conducted by RHB Islamic Banking and Pusat Pungutan Zakat (PPZ) Majlis Agama Islam Wilayah Persekutuan (MAIWP) to get their views and perceptions as well as the potential application of Zakat Wakalah for sustainable development of Islamic social finance in Malaysia and analyzed using thematic analysis. The results revealed the potential use of Zakat Wakalah in allowing zakat payers to request a Zakat refund of a particular portion for self-distribution to identify eligible zakat recipients or Asnaf. Its application is practical, especially in Islamic social finance activities in Islamic banking and finance, as one of the effective ways of distributing Zakat to Asnaf since the issue of ineffective distribution from the Zakat authority is perceived by society. Thus, the application of Zakat Wakalah lets individuals or companies distribute Zakat Wakalah by themselves.